2006
DOI: 10.1016/j.cell.2006.06.043
|View full text |Cite
|
Sign up to set email alerts
|

ZO-1 and ZO-2 Independently Determine Where Claudins Are Polymerized in Tight-Junction Strand Formation

Abstract: A fundamental question in cell and developmental biology is how epithelial cells construct the diffusion barrier allowing them to separate different body compartments. Formation of tight junction (TJ) strands, which are crucial for this barrier, involves the polymerization of claudins, TJ adhesion molecules, in temporal and spatial manners. ZO-1 and ZO-2 are major PDZ-domain-containing TJ proteins and bind directly to claudins, yet their functional roles are poorly understood. We established cultured epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
626
6
11

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 716 publications
(707 citation statements)
references
References 65 publications
48
626
6
11
Order By: Relevance
“…We speculate that this is due to the functional redundancy between ZO-1 and ZO-2, another member of the membrane-associated guanylate kinase homologue family (15). The speculation is strongly supported by a recent report describing that in the absence of ZO-1, some physiological functions of ZO-1 are compensated for by ZO-2 in the polarized epithelial cells (56). We confirmed that ZO-2 is expressed in Caco/B7 and HeLa cells and is also recruited to the pedestals and the actin tails (our unpublished observation).…”
Section: Discussionsupporting
confidence: 70%
“…We speculate that this is due to the functional redundancy between ZO-1 and ZO-2, another member of the membrane-associated guanylate kinase homologue family (15). The speculation is strongly supported by a recent report describing that in the absence of ZO-1, some physiological functions of ZO-1 are compensated for by ZO-2 in the polarized epithelial cells (56). We confirmed that ZO-2 is expressed in Caco/B7 and HeLa cells and is also recruited to the pedestals and the actin tails (our unpublished observation).…”
Section: Discussionsupporting
confidence: 70%
“…Occludin and JAM-1 were shown to be associated with ZO-1 through both non-PDZ and PDZ domains Schmidt et al, 2004). Recent studies on ZO-1/2/3-deficient cultured epithelial cells have revealed unequivocally that ZO-1/2 determines where and when the claudins are polymerized to form TJ strands with barrier functions (Umeda et al, 2006). These cells lacking in ZO-1/2/3, are normal in their basic apico-basal polarity, but are abnormal in the fine distribution of polarity proteins, such as PAR3, suggesting that tight junctions might be involved in the fine-tuning of cell polarity, although they are probably not involved in the initiation of apico-basal polarity.…”
Section: Molecular Bases For Tjmentioning
confidence: 99%
“…At the present time, several aspects of the molecular mechanisms of TJ physiology have been implied by cellular and molecular biology studies, as described below, although the detailed molecular mechanisms still remain unclear. First, ZO-1/2-deficient cultured epithelial cells, which form epithelial cell sheets but lack TJs (Umeda et al, 2006), exhibited no paracellular barrier functions, but did exhibit the normal epithelial cell sheet formation (mediated by cell-cell adhesion through the belt-like arrangement of AJs). Thus, the proteinaceous TJ strands are dominantly responsible for the paracellular barrier functions, consistent with the dominant contribution of TJs, compared with the minor contribution of the lateral intercellular space, to paracellular resistance that was revealed by physiological measurements (Kottra et al, 1993a; Kottra and Fro¨mter, 1993b; Yap et al, 1998).…”
Section: Mysterious Molecular Mechanisms Of Tj Physiology Implied By mentioning
confidence: 99%
“…ZO1(ko)/2(kd) Eph4 cells and ZO1(ko)/2(ko) F9 cells were established by Umeda et al (2006). Eph4 and F9 cells with or without ZO-1/2 were cultured in DMEM including 10% fetal calf serum.…”
Section: Cell Culturementioning
confidence: 99%